'Cultivated Idleness': Carlyle, Wilde, and Victorian representations of creative labour. Issue 1 (2nd January 2016) - Mitchell, Rebecca N.
Abstract: This article defines two visions of artistic creation prevalent in the mid-to-late nineteenth century. The first is typified by Ford Madox Brown's Work (1852–65), an image that champions the nobility of physical labour, and sees its literary rendering in Thomas Carlyle's œuvre. Using the story of the writing and destruction of Carlyle's French Revolution manuscript as a guiding example, it is argued that a narrative equating intellectual and creative production with hard, physical labour was consciously developed and mediated by the press and public. While this model of authorial industry and effort has for many come to stand for high Victorian creative agency, it was not uncontested in its time. In contrast, the article traces an equally compelling, concurrent counter-narrative, one that was codified by Henry Wallis's post-Romantic image of the dying poet Chatterton and which was exemplified in Oscar Wilde's affectation of authorial indolence. These contrasting versions of artistic agency demonstrate the negotiation of creative labour that defined the reception of British authors and their work from the 1850s to the fin de siècle.